Drug-induced hepatopathies in primary care – what to remember in practice and how to proceed - Woroń, Jarosław; Drobnik, Jarosław (Family Medicine & Primary Care Review, 2024)
Drug-induced liver injury is a common cause of liver dysfunction, although making the correct diagnosis is not easy. Even though it is becoming more common, it often remains undiagnosed. The clinical picture of drug-induced liver injury is diverse and ranges from a slight, often transient increase in the activity of liver indicator enzymes to acute liver failure. In practice, it is important to proceed appropriately after the diagnosis of drug-induced hepatopathy and to select the most optimal pharmacotherapy for drug-induced liver injury. In the treatment of drug-induced hepatopathies dietary supplements and products containing milk thistle should be avoided. Milk thistle extracts inhibit the activity of cytochrome P450–CYP3A4, CYP2D6 and CYP2C9 isoenzymes, inducing interactions with many drugs, which may result in drug-induced hepatopathies, also in cancer patients. There are no studies supporting the use of silymarin in drug-induced liver injuries. Higher caution should be exercised when using products with cholagogenic and choleretic properties. In clinical practice, it is worth remembering that in the event of adverse reactions such as hepatotoxicity induced by pharmacotherapy, the most effective treatment should be implemented based on available medicinal products. Random selection of drugs should be strictly avoided in order to reduce the risk of incorrectly selected pharmacotherapy.